News and Commercials: Binding Deficits for Complex Information in Schizophrenia - Sejunaite, Karolina; Lanza, Claudia; Gaucher, Frederic; Klug, Roland; Riepe, Matthias W. (Frontiers in Psychiatry, 2021)
Memory for complex content is severely impaired in patients with schizophrenia spectrum disorders, which might make processing of daily information such as news and commercials particularly challenging. The goal of the present study was to assess the impairment of everyday memory in patients with schizophrenia. Healthy controls (HC) and patients with schizophrenia (SZ) were asked to watch a selection of six news segments and six commercials and complete a recognition task on the content of these video clips. All participants completed a neuropsychological test battery comprising measures of attention, working and episodic memory, and executive function. The total number of correctly recognized items was significantly lower in the SZ group. In contrast, the number of false recognitions was alike in both news and commercials paradigm. We conclude that memory in patients with schizophrenia is more prone to omissions than distortions for complex everyday stimuli. The results offer further support for impaired binding in SZ patients. Memory in SZ suffices to reject false multi-feature items on grounds of identifying at least one feature as incorrect but does not suffice to recall all features of a complex item and affirm it as correct.